Farming systems and integrated pest management - Varma, Anupam; Verma, J. P. (Jeevan P.); Indian Science Congress Association. Session 1990 : Cochin, India) (New Delhi : Malhotra Pub. House, 1992)
Contributed papers.
"Proceedings symposium section of Agricultural Sciences 77th Session of the Indian Science Congress Cochin, 1990"--Added t.p.
Cover title: Farming systems & integrated pest management.
Includes bibliographical references.
Mode of access: Internet.
Keywords: Pests -- Integrated control; Agricultural systems; Agricultural pests -- Integrated control; Agricultural systems -- India -- Congresses; Pests -- Integrated control -- India -- Congresses; Agricultural pests -- Integrated control -- India; India; Conference papers and proceedings